Design of a Low Cost High Efficiency Multiple Output Self Oscillating Flyback Converter - Yogi Sawitra; Prapto Nugroho; Eka Firmansyah; Wahyu Dewanto; Rudy Hartanto; Tiyono Tiyono; Tumiran Tumiran (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2017)
The use of some integrated circuits in an SMPS circuit are the main factor that increasing the cost. Self-oscillating feedback converter topology is a well-known circuit topology for low-cost application without using any single integrated circuit chip. In this paper, a Low Cost with high efficiency converter without any single integrated circuit component was analysed and designed. It has also multiple outputs of 3.3 V/1 A, 5 V/0.5 A, and 12 V/0.1 A so that it can be used as power supply for DVD player. Experiment results showed that it can deliver continuously output voltage as designed and a total output power of 7.3 W, with an efficiency for about 70%.